Physical and chemical changes during the ripening of Saba bananas (Compresa blanco Teodoro) - Rivero, Filipinas C.
A preliminary investigation on the variations of some physical and chemical properties of Saba bananas with maturity was made. Fruit size, penetrometer readings, pulp-peel ratio, respiration rate, percent titratable acidity, percent soluble solid, and pectin content were found to increase with maturity while pH, Bric-acid ratio, starch content decreased with maturity. Color, weight, texture, starch, sugar, acid, and pectin changes were determined at different stages of ripening to disclose the physical and chemical changes during the ripening of Saba bananas. The pulp-peel ratio, penetrometer readings, sugar acid, and pectin contents were found to increase as ripening proceeded. The pH and starch content decreased with ripening.